INTEGRATED PERFORMANCE MANAGEMENT MODEL OF COMPANY USING AN ANALYTICAL HIERARCHY PROCESS - Tadić, Jelena; Mihajlović, Milan (Poslovna ekonomija, 2020)
The aim of this paper is to test the application of an integrated performance management model on the example of a manufacturing company in the field of food industry in Serbia. The proposed model integrates performance quantification (objective and subjective) on the one hand, and performance improvement, on the other. Objective variables are presented in the form of cost and time dimensions, while analytical hierarchical process (AHP) was used to quantify subjective variables. The research results provide insight into the achieved and optimal performance of the company, which provides a basis for further performance improvements.
Keywords: Integrated Performance Management Model, Analytical Hierarchy Process, Food industry.